Protecting the protector: Laws regarding wetlands in Malaysia - Sharom, A.; Loganathan, M.T. (2005)
Wetlands such as coastal mangroves take up the least amount of space compared to other types of forest areas in Malaysia, and yet, percentage wise, they face the greatest destruction. Their value as storehouses of biological diversity, breeding grounds for marine life and water purifier, is oft overlooked for the sake of economic "development" . The recent Tsunami disaster drove home another importance of coastal mangroves which has been sadly ignored and that is as a buffer between large waves and the coast. It was acknowledged by the Malaysian Prime Minister that the lack of mangroves due to their destruction for "development" purposes exacerbated the problem in Malaysia, particularly the island of Penang. This paper shall examine the laws in Malaysia that can be used to protect our mangroves in a critical light. It shall then proceed to make suggestions for change to ensure that such a precious resource is not lost.